Assessment of Conduit-Assisted Primary Nerve Repair Strength With Varying Suture Size, Number, and Location. (November 2019) - Babovic, Nikola; Klaus, Derek; Schessler, Matthew J.; Schimoler, Patrick J.; Kharlamov, Alexander; Miller, Mark C.; Tang, Peter
Background: Outcomes following digital nerve repair are suboptimal despite much research and various methods of repair. Increased tensile strength of the repair and decreased suture material at the repair site may be 2 methods of improving biologic and biomechanical outcomes, and conduit-assisted repair can aid in achieving both of these goals.Methods: Ninety-nine fresh-frozen digital nerves were equally divided into 11 different groups. Each group uses a different combination of number of sutures at the coaptation site and number of sutures at each end of the nerve-conduit junction, as well as 2 calibers of nylon suture. Nerves were transected, repaired with these various suture configurations using an AxoGuard conduit, and loaded to failure.Results: The 2-way analysis of variance (ANOVA) showed that repairs performed with 8-0 suture have significantly higher maximum failure load compared with 9-0 suture repairs ( P < .01). Increasing the number of sutures in the repair significantly increased the maximum failure load in all groups regardless of suture caliber used ( P < .01). Repairs with 9-0 suture at the coaptation site did not jeopardize repair strength when compared with 8-0 suture.Conclusions: Conduit-assisted primary digital nerve repairs with 8-0 suture increases the maximum load to failure compared with repairs with 9-0 suture, as does increasing the overall number of sutures. Using 9-0 suture at the coaptation site with 8-0 suture at the nerve-conduit junction does not jeopardize tensile strength when compared with similar repairs using all 8-0 suture and may decrease inflammation at the repair site while still achieving sufficient tensile strength.